ANALISIS PERBANDINGAN KINERJA KEUNGANAN SELAMA PANDEMI COVID-19 PADA BANK YANG TERDAFTAR INDEX LQ-45 - Marito, Anggi Sinta; Moh Athoillah (Contemporary Studies in Economic, Finance and Banking, 2022)
This study aims to analyze the financial performance of banks during the iCovid-19 pandemic with a sample of banking studies listed on the LQ45-Index, to find out whether there are differences in financial performance during the pandemic. This analysis uses the ratio of CAR (Capital Adequency Ratio), ROA (Return On Assets), and LDR/FDR (Loan Deposit Ratio) or (Financing to Deposit Ratio). This study uses a quantitative method with a comparative approach, because this study uses numbers and is analyzed using statistics. This study uses data from the publication of the Financial Statements Quarter I – Quarter IV 2019-2020. The population of this study was taken from the banks listed on the LQ45-Index for the 2019-2020 period, which amounted to six banks, namely Bank Central Asia (BCA), Bank Rakyat Indonesia (BRI), Bank Negara Indonesia (BNI), Bank Mandiri, Bank Tabungan Negara ( BTN), and the Sharia State Pension Savings Bank (BTPN). The statistical method used is the Shapiro-Wilk normality test and the Paired Sample T-Test. The results showed that in the three BCA there were significant differences in financial performance during the Covid-19 pandemic, BRI's CAR and ROA ratios had significant differences in financial performance during the Covid-19 pandemic, while BNI, Bank Mandiri, BTN, and BTPN Syariah did not have differences in financial performance during the pandemic for ROA and LDR ratios, only the CAR ratio shows differences in financial performance during the pandemic